(untitled) (Journal of The Colloquium for Information Systems Security Education, 2025)
This paper describes the design, implementation and first delivery of a no-cost, no-credit, multi-week virtual bootcamp called Cyber Bridge. The motivation underlying Cyber Bridge is to cast a wider recruitment net by easing the transition of students – especially those from non-technical academic preparations – into cybersecurity studies, particularly at the graduate level. It provides background insights regarding the inception and evolution of the Cyber Bridge project, experimental methodologies and observations, and findings based on analysis of collected metrics and feedback. Results support the view that a Cyber Bridge is a reasonable approach to: increasing students’ comfort level regarding virtual learning environments; introducing and reviewing some cybersecurity foundations; connecting students to additional resources to improve upcoming academic experiences; and moderating their confidence by recognizing knowledge gap areas they may need to review or remediate. Future direction ideas and recommendations are shared that align with a longer-term vision to mobilize this capability to empower more underrepresented, underserved individuals to succeed as cybersecurity professionals and researchers.